2019
DOI: 10.1097/sap.0000000000001669
|View full text |Cite
|
Sign up to set email alerts
|

Early Functional Outcomes After Prepectoral Breast Reconstruction

Abstract: Introduction Staged, tissue expander-based implant reconstruction continues to be the most common mode of breast reconstruction after mastectomy and has evolved significantly for the past 60 years. Prepectoral acellular dermal matrix (ADM)-assisted breast reconstruction is gaining popularity with complication rates similar to total submuscular and ADM-assisted partially submuscular reconstruction. Ours is among the first reports comparing postoperative pain and early functional outcomes between 2-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…These data concur with recent studies showing similar pain within the first 1 to 2 postoperative weeks following subpectoral or prepectoral tissue expander placement 14,22 but differ from smaller studies that report less pain in prepectoral reconstruction patients. 19,21,25 Studies that include a mix of patients receiving both direct-to-implant and tissue expander…”
Section: Discussionmentioning
confidence: 99%
“…These data concur with recent studies showing similar pain within the first 1 to 2 postoperative weeks following subpectoral or prepectoral tissue expander placement 14,22 but differ from smaller studies that report less pain in prepectoral reconstruction patients. 19,21,25 Studies that include a mix of patients receiving both direct-to-implant and tissue expander…”
Section: Discussionmentioning
confidence: 99%
“…Schaeffer et al reported early functional outcomes following prepectoral breast reconstruction in comparison with subpectoral breast reconstruction [33]. They showed that the prepectoral groups had significantly lower inpatient pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Two studies evaluated upper extremity and shoulder function, with more rapid recovery and less upper extremity morbidity than partially submuscular patients. 43,52 One patient series demonstrated fewer morphine equivalents administered after prepectoral reconstruction than in a partially submuscular implant placement cohort. 43 Fewer postoperative visits and more rapid expansion have been demonstrated with prepectoral breast reconstruction when compared with subpectoral techniques, which can improve patient satisfaction with recovery.…”
Section: Functional Outcomes Postoperative Pain and Recoverymentioning
confidence: 99%
“…Meshing and fenestrating the acellular dermal matrix to increase its functional surface area 26 while stabilizing cost have been described, as has orienting mesh differently based on breast base width. 43 Meshing or fenestrating acellular dermal matrices would create potential space for native capsule formation that may increase capsular Copyright © 2021 American Society of Plastic Surgeons. Unauthorized reproduction of this article is prohibited.…”
Section: Perioperative Safety Outcomes Of Prepectoral Reconstructionmentioning
confidence: 99%